Volume change behaviour of compacted residual clay / Mohd Yusri Salim - Salim, Mohd Yusri (1997)
A study on the volume change behaviour on compacted clay was made oh disturbed sample. Soil samples were taken from site and were tested in soil laboratory .The type of test conducted were particle size analysis, atterberg limit test, Compaction test and lastly triaxial compression test. A series of test were performed in accordance with British Standard 1377 : 1975 method of test for soils for Civil Engineering purpose. The soil sample can be classification as CLAY silt high plasticity. Cell pressure applied to the specimens was estimated between lOOkPa to 600kPa. Base on the data gathering true testing carried out in laboratory, nevertheless, finding of this study are able to reflect to the relationships between cell pressure duration and volume change.